Identification of Key Genes and Pathways in Persistent Hyperplastic Primary Vitreous of the Eye Using Bioinformatic Analysis - Thomas, Derin M.; Kannabiran, Chitra; Balasubramanian, D. (Frontiers in Medicine, 2021)
Background-Persistent Hyperplastic Primary Vitreous (PHPV) is a congenital disorder of the eye caused due to the failure of normal regression of embryonic hyaloid vascular system. The molecular pathways, the candidate genes or the drug targets of PHPV remains poorly understood. The present paper describes a detailed study to identify the key genes and molecular pathways associated with PHPV and to explore potential therapeutic agents for the management of the disease using bioinformatic analysis. Methods-Genes associated with PHPV were detected using the text mining tool pubmed2ensembl, and assigned Gene Ontology (GO) biological process terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways using the GeneCodis program. The protein-protein interaction (PPI) network was constructed from the Text Mining Genes (TMGs) by STRING and visualized in Cytoscape. Module analysis was performed using the Molecular Complex Detection (MCODE) plugin, and GO and KEGG analyses of the gene modules were performed using the Database of Annotation, Visualization and Integrated Discovery (DAVID) platform. The genes that clustered in the significant module were selected as hub genes, and functions and pathways of the hub genes were visualized using ClueGO and CluePedia and ShinyGo. Finally, the drug-gene interaction database was used to explore drug–gene interactions of the hub genes to find drug candidates for PHPV. Results-Total of 50 genes associated with PHPV were identified.Gene functional enrichment analysis yielded 35 enriched GO terms and 15 associated KEGG pathways. The PPI network that included thirty-one nodes with forty-two edges was constructed, and two gene modules were obtained using the MCODE. We selected 14 hub genes as core candidate genes such as TP53, VEGFA, SMAD2, CDKN2A, FOXC, FZD4, LRP5, KDR, FZD5, PAX6, MYCN, NDP, PITX2 and PAX2 primarily associated with camera type eye morphogenesis, pancreatic cancer, apoptotic process involved in morphogenesis and VEGF receptor signaling pathway. We found that 7 of the 14 selected genes could be targeted by 26 FDA approved existing drugs. Conclusions- In conclusion, the results identified a total of 14 potential genes,4 significant pathways and 26 candidate drugs which could provide basis of novel targeted therapies as potential treatment for the management of PHPV.